y=(pie)^(x)+x^(pie) work out step by step please
Follow Math Help Forum on Facebook and Google+
Originally Posted by ashley09 y=(pie)^(x)+x^(pie) work out step by step please Once again, show us an attempt. We're not here to do your homework.
Originally Posted by ashley09 y=(pie)^(x)+x^(pie) work out step by step please The second term is dealt with in the usual way using the formula $\displaystyle \frac{d (x^a)}{dx} = a \cdot x^{a-1}$. The first term is dealt with using the formula $\displaystyle \frac{d (a^x)}{dx} = (\ln a) \, a^x$.
View Tag Cloud